Studies of the Effect of Crosslinking in the Strongly Basic Anion Exchanger Dowex 1 and the HNO Concentration Employed on the Separation of the Sm–Nd Pair in the Polar Organic Solvent–HO–HNO System - Z. Hubicki; M. Olszak (Adsorption Science & Technology)
Because of their specific structure, rare earth elements are used for the modification or structural stabilization of many metallic or ceramic materials employed in modern technology and also in the metallic form, i.e. in alloys and compounds with unique properties. Industrial demand for rare earth metals has increased lately due to their new application possibilities, e.g. in supermagnets of the Nd–Fe–B type or in ceramic high-temperature superconductors. Equally, the application of rare earth elements in metallurgy, catalysis, ceramics, etc. remains of significant importance. The separation and purification of rare earth elements(III) which occur in groups with similar physicochemical properties involve extremely difficult and complex processes. Ion exchange is one method which enables such separation. This paper presents the results of studies of the influence of the extent of crosslinking in the anion exchanger Dowex 1 and the concentration of nitric acid on the separation of the Sm III –Nd III pair by frontal analysis in 90% v/v CH 3 COCH 3 – or the CH 3 OH–10% v/v × M HNO 3 systems. The most effective results were obtained in the 90% v/v CH 3 OH–10% v/v 7 M HNO 3 system employing the anion exchanger Dowex 1 × 4 allowing 0.11 kg samarium(III) to be purified on 1 dm 3 ion exchanger in the nitrate form and leading to a decrease in the micro-component content to a value below 10 −3 %.